Effect of ocrelizumab on vaccine responses in patients with multiple sclerosis: The VELOCE study. (6th October 2020) - Bar-Or, Amit; Calkwood, Jonathan C.; Chognot, Cathy; Evershed, Joanna; Fox, Edward J.; Herman, Ann; Manfrini, Marianna; McNamara, John; Robertson, Derrick S.; Stokmaier, Daniela; Wendt, Jeanette K.; Winthrop, Kevin L.; et al.
Abstract : Objective: The phase IIIb A Study to Evaluate the Effects of Ocrelizumab on Immune Responses in Participants With Relapsing Forms of Multiple Sclerosis (VELOCE) study (NCT02545868) assessed responses to selected vaccines in ocrelizumab (OCR)-treated patients with relapsing multiple sclerosis. Methods: Patients were randomized 2:1 into the OCR group (n = 68; OCR 600 mg) or control group (n = 34; interferon beta or no disease-modifying therapy). All received tetanus toxoid (TT)-containing vaccine, Pneumovax (23-valent pneumococcal polysaccharide vaccine [23-PPV]), and keyhole limpet hemocyanin (KLH). The OCR group was subdivided into OCR1 (n = 33) and OCR2 (n = 35) at randomization. The OCR1 group received Prevnar (13-valent conjugate pneumococcal vaccine) 4 weeks after 23-PPV; the OCR2 and control groups received influenza vaccine. Vaccinations started 12 weeks after OCR initiation (OCR group) or on day 1 (control group). Results: Positive response rate to TT vaccine at 8 weeks was 23.9% in the OCR vs 54.5% in the control group. Positive response rate to ≥5 serotypes in 23-PPV at 4 weeks was 71.6% in the OCR and 100% in the control group. Prevnar did not enhance response to pneumococcal serotypes in common with Pneumovax. Humoral response to KLH was decreased in the OCR vs control group. Seroprotection rates at 4 weeks against 5 influenza strains ranged from 55.6% to 80.0% in the OCR2 group and 75.0% to 97.0% in the control group. Conclusion: Peripherally B-cell–depleted OCR recipients mounted attenuated humoral responses to clinically relevant vaccines and the neoantigen KLH, suggesting that use of standard nonlive vaccines while on OCR treatment remains a consideration. For seasonal influenza vaccines, it is recommended to vaccinate patients on OCR because a potentially protective humoral response, even if attenuated, can be expected. Classification of evidence: This study provides Class II evidence confirming that the humoral response to nonlive vaccines in patients with relapsing multiple sclerosis after OCR treatment is attenuated compared with untreated or interferon beta–treated patients, but they can still be expected to be protective. Clinicaltrials.gov identifier: NCT02545868.